Scenic perennial plants classification - Jumayeva Dilnoza Abdusattar qizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Earth sphere flora most of them a lot yearly plants enters. A lot yearly scenic plants floral landscape harvest in doing important important has of plants land over part each year in winter dead will be, the root or onions preserved remains. In the spring while from him new stems grow up comes out A lot yearly of plants to live term sharp differs and one how many from from 10 to 100 years, sometimes even 1000 years can A lot yearly scenic plants to the group tulip, velvet or bellflower, marigold, chamomile, potato flower, safflower, safflower and others enters.